DEPORTATION AND PRO JUSTITIA COMPULSORY MECHANISM: THE PREVENTION REMEDY OF ABUSE OF POWER AND HUMAN RIGHTS UPHOLDING - I Nyoman Gede Surya Mataram; Widodo Ekatjahjana; I Gede Widhiana Suarda; A’an Efendi (CV. RADJA PUBLIKA, 2025)
One of the sources of Non-Tax State Revenue increasing comes from the Administrative Sanctions of Immigration. The enforcement of the sanction is followed up by the deportation of the foreigners who violate the law in Indonesian territory. The juridical basis for this authority is the attribution regulated in Law Number 6 of 2011 concerning Immigration and its derivatives. In practice, the implementation of Article 75 of Immigration Regulation is disrupted which has resulted the human rights protection is not accommodated as stipulated in Article 9 of Declaration of Human Rights and also Article 34 Law Number 39 of 1999. This cannot be allowed in the name of the Principle of Legal Certainty, Transitional Justice, and Global Justice. The result must refer to the declaration agreed upon at United Nations, in which Article 34 stipulates that “every person shall not be exiled or disposed arbitrarily”. This article is an arrangement in Article 9 of the Universal Declaration of Human Rights. Thus, this article must be added to the legal substance regarding the obligation to have a judge’s verdict with permanent legal force from the court in Indonesia against the foreigners who violate the Law. This commitment must also be applied in all legislative products stipulated by the government as the legislator. This includes all legal regulations in Immigration.